HUBUNGAN KARAKTERISTIK DENGAN TINGKAT PENDAPATAN PETERNAK AYAM RAS PEDAGING DI KECAMATAN TAMBUSAI UTARA - -, Sehat (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2016)
This research aims to examine the characteristics of the relationship with income level broiler farms in the District of North Tambusai. This research uses questionnaire data directly from broiler breeders. Variables include age, education and experience. Data was analyzed using SPSS 17. The results showed that the correlation analysis model the characteristics of the income level of broiler breeders in the district of North Tambusai by the following equation: Y = 0000 to 0.140 X1 + 0.420 X2 + X3 + 0.166 2810401.581 it shows that independent variables of age, education and experience have a very strong relationship with the income of farmers in the district of North Tambusai. Classical assumption test results showed that age, education and experience real effect because the level of significance above 5% (0.05).